Vers un nouveau genre de finance ? - Gunther Capelle-Blancard; Jézabel Couppey-Soubeyran; Antoine Rebérioux (Revue de la Régulation)
In this article, we review gender studies in finance. Based on an original analysis of a French household survey (Insee-Pater survey), we first document differences across gender in preferences and behaviors in finance. We then examine the consequences of these differences in terms of saving and portfolio choices, regarding the use of banking and financial services, decisions made by agents in the banking and financial industry, corporate governance and, finally, regarding teaching and research practices by academics in finance. We highlight five main findings. (i) The Pater survey supports the existence of differences across gender in preferences and behavior; (ii) these differences are to a large extent driven by the fact that people unconsciously cling to gender-type stereotypes; (iii) whatever their causes, these differences result in rather negative outcomes for women in terms of portfolio choices and credit access; (iv) these differences are highly dependent on the context and individual past experience, including education in finance; (v) the literature has not so far produced convincing evidence of a “female-style” of leadership when women succeed in breaking the glass ceiling for top positions in the financial or non-financial sectors, and in firms, regulatory bodies or academia.